Magnetic Mesoporous Silica Composite for Enhanced Preconcentration of Selected Organophosphorus Pesticides in Fruits - Nur Husna Zainal Abidin; Wan Nazihah Wan Ibrahim; Nor Suhaila Mohamad Hanapi; Nor’ashikin Saim (Indonesian Journal of Chemistry, 2020)
In the present work, MCM-41 coated magnetic particles (Fe3O4-MCM-41) composite was synthesized and employed as an effective adsorbent in magnetic solid phase extraction (MSPE) of three selected organophosphorus pesticides (OPPs) namely chlorpyrifos, diazinon and parathion methyl from grape and strawberry samples prior to high performance liquid chromatography with UV detection (HPLC-UV). The synthesized sorbent was physicochemically and morphologically characterized via Fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and N2 adsorption analysis. The main parameters on the extraction efficiency of selected OPPs, including extraction time, desorption solvent, desorption time, and sorbent dosage, were thoroughly optimized. Compared to MCM-41 sorbent, the newly synthesized Fe3O4-MCM-41 adsorbent shows a linear response (0.1-5.00 mg L–1) with good determination coefficients ranging from 0.9900 to 0.9980, low limits detection (LODs), 0.02-0.15 mg L–1 and low limit quantifications (LOQs), 0.06-0.40 mg L–1. The precision as relative standard deviation (%RSD) of the proposed MSPE method was studied at low and high concentration (0.1-5.0 mg L–1) based on intra-day (1.0 to 6.0%, n = 3) and inter-day (1.0 to 7.0%, n = 3), respectively. Fruit matrices were used to assess the field applicability of the sorbents. Comparatively, Fe3O4-MCM-41 achieved excellent percent recovery (85–120%) compared to the MCM-41 (70–110%). The result revealed that the Fe3O4-MCM-41 composite was efficient sorbent with good capability for the preconcentration of selected OPPs from fruit samples.